Economic Issues with Certified and Farmer-Saved Wheat Seed - Boland, Michael; Dhuyvetter, Kevin C.; Howe, Matt (My University, 2001)
This publication discusses the economic impliactions with certified and farmer-saved wheat seeds in Kansas.
MF2498_2001_01
Keywords: MF2498; MF